Localization of angiotensin receptor type 2 in fetal bovine ovaries - Portela, V. M.; Castilho, A. C. [UNESP]; Bertolin, K.; Buratini, J. [UNESP]; Price, C. A. (Elsevier B.V., 2016)
In the ovary, angiotensin II (ANGII) acts through the type 2 receptor (AGTR2) to induce ovulation and may play a role in follicle atresia. In this study, we determined the expression of AGTR2 mRNA and protein during follicle formation in the bovine ovary. Female fetuses at different gestational ages (60, 75, 90, 120, 150 and 210 days) were used for immunolocalization of AGTR2. At day 60, AGTR2 was localized to the cytoplasm of oogonia; from days 75 to 150, during follicle formation and development to secondary stage, AGTR2 immunostaining was weak and irregular, but from day 210 staining became evident in granulosa cells of preantral follicles and in both granulosa and theca cells of small antral follicles. These data differ from those in pigs, in which AGTR2 protein is detected in preantral follicles throughout gestation. Abundance of AGTR2 mRNA in whole ovaries did not change with fetal age. In conclusion, AGTR2 protein is expressed in ovigerous cords in fetal bovine ovaries but not in preantal follicles until the formation of antral follicles. These data suggest important species-specific differences in the expression of AGTR2 in fetal ovaries from polypvulatory and monovulatory animals. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Preantral follicle; AT2; Angiotensin; Ovigerous chord; Fetal ovary